Impact of education and communication on behaviour change - Udoudom, Uduak Imoh; Aondowase, Saawuan; Igiri, Anthony (Yayasan Mitra Persada Nusantara, 2023)
This paper delved into the intricate relationship between educational interventions and communication strategies in the context of fostering significant behaviour change. With a focus on comprehensive exploration, the investigation aimed to uncover the synergistic effects of these two key components in influencing individuals' behaviours positively. Through an extensive literature review, various educational interventions and communication strategies were identified, ranging from traditional didactic methods to innovative technology-driven approaches. The study explored how these interventions were strategically communicated to target audiences across diverse settings, including healthcare, education, and environmental conservation. The study underscores the pivotal role of effective communication strategies as a catalyst for enhancing the impact of educational interventions on behaviour change. The findings will contribute to a deeper understanding of the interplay between these two components and offer valuable insights for practitioners, policymakers, and researchers seeking to design and implement comprehensive behaviour change initiatives.